GAMBARAN COLLEGE ADJUSTMENT MAHASISWA BARU DI MASA PANDEMI COVID-19 - Shinta Vionita; Rahmah Hastuti (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
College adjustment comes from adjustment, which means the adjustment of students to the environment in college.  The way students adjust during the first year of college is a prediction of significant life events later in their college career. In college adjustments, there are four dimensions, including academic adjustment, social adjustment, personal emotional adjustment, and goal commitment institutional attachment. This study aims to find an overview of first year college students during the Covid-19 pandemic. This study had 345 freshman college students as participants ranging in age from 18 to 25 who were studying at universities in Jakarta. The measuring instrument used was the Student Adaptation to College Questionnaire (SACQ). Based on the results of data processing carried out to describe college adjustment of first year college students during the Covid-19 pandemic using descriptive methods and different demographic data tests, it was found that college adjustments had differences in the gender of men and women, and had no differences in the type of college, age, faculty, and current residence. The results of this study can also be concluded that the dimension of goal commitment to institutional attachment has the highest mean value, followed by social adjustment, academic adjustment, and the lowest is personal emotional adjustment. This study also describes the high level of college adjustment based on its dimensions. College adjustment berasal dari adjustment yang artinya penyesuaian mahasiswa dengan lingkungan perguruan tinggi. Cara mahasiswa menyesuaikan selama tahun pertama kuliah merupakan prediksi peristiwa kehidupan yang signifikan di kemudian hari dalam karir perguruan tinggi. Dalam college adjustment, terdapat empat dimensi, antara lain academic adjustment, social adjustment, personal emotional adjustment, dan goal commitment institutional attachment. Penelitian ini bertujuan untuk mengetahui gambaran umum college adjustment mahasiswa baru di masa pandemi Covid-19. Penelitian ini memiliki 345 partisipan mahasiswa baru dengan rentang usia antara 18 hingga 25 tahun yang berkuliah di perguruan tinggi di daerah Jakarta. Alat ukur yang digunakan adalah Student Adaptation to College Questionnaire (SACQ). Berdasarkan hasil olah data yang dilakukan untuk menggambarkan college adjustment mahasiswa baru di masa pandemi Covid-19 dengan menggunakan metode deskriptif dan uji beda data demografi, didapatkan hasil bahwa college adjustment memiliki perbedaan pada jenis kelamin laki-laki maupun perempuan, serta tidak memiliki perbedaan pada jenis perguruan tinggi yang dipilih, usia, fakultas, dan tempat tinggal saat ini. Hasil penelitian ini juga dapat disimpulkan bahwa dimensi goal commitment institutional attachment memiliki nilai mean yang paling tinggi, disusul dengan social adjustment, academic adjustment, dan yang paling rendah adalah personal emotional adjustment. Penelitian ini juga menggambarkan tingkat tinggi rendahnya college adjustment berdasarkan dimensinya.